James J. Dinsmore letter to Nicholas S. Halmi regarding bird sightings - Dinsmore, James J.et al
Letter and field notes from James J. Dinsmore to Nicholas S. Halmi, reporting bird sightings by type. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1977. Epson - sheet feed/flatbed